Hippo Pathway Gene Mutations in Malignant Mesothelioma. Issue 5 (May 2015) - Miyanaga, Akihiko; Masuda, Mari; Tsuta, Koji; Kawasaki, Kumiko; Nakamura, Yuka; Sakuma, Tomohiro; Asamura, Hisao; Gemma, Akihiko; Yamada, Tesshi
<x xml:space="preserve">Abstract</x> Introduction: Malignant mesothelioma (MM) is an aggressive neoplasm causatively associated with exposure to asbestos. MM is rarely responsive to conventional cytotoxic drugs, and the outcome remains dismal. It is, therefore, necessary to identify the signaling pathways that drive MM and to develop new therapeutics specifically targeting the molecules involved. Methods: We performed comprehensive RNA sequencing of 12 MM cell lines and four clinical samples using so-called next-generation sequencers. Results: We found 15 novel fusion transcripts including one derived from chromosomal translocation between the large tumor suppressor 1 (LATS1) and presenilin-1 (PSEN1) genes. LATS1 is one of the central players of the emerging Hippo signaling pathway. The LATS1–PSEN1 fusion gene product lacked the ability to phosphorylate yes-associated protein and to suppress the growth of a MM cell line. The wild-type LATS1 allele was undetectable in this cell line, indicating two-hit genetic inactivation of its tumor suppressor function. Using pathway-targeted exon sequencing, we further identified a total of 11 somatic mutations in four Hippo pathway genes (neurofibromatosis type 2 [NF2], LATS2, RASSF1, and SAV1) in 35% (8 of 23) of clinical samples. Nuclear staining of yes-associated protein was detected in 55% (24 of 44) of the clinical samples. Expression and/or phosphorylation of the Hippo signaling proteins, RASSF1, Merlin (NF2), LATS1, and LATS2, was frequently absent. Conclusions: The frequent alterations of Hippo pathway molecules found in this study indicate the therapeutic feasibility of targeting this pathway in patients with MM.